Effects of Pesticides Used on Table Grapes on the Mealybug Parasitoid Coccidoxenoides peregrinus (Timberlake) (Hymenoptera: Encyrtidae) - Walton, V.M.; Pringle, K.L. (South African Journal of Enology and Viticulture, 2017)
The effects of regularly used table grape insecticides and fungicides on 1-day-old adults of the parasitoid Coccidoxenoides peregrinus (Timberlake) of vine mealybug, Planococcus ficus (Signoret), were determined in the laboratory. The insecticides chlorpyrifos, endosulfan and cypermethrin were highly toxic to the parasitoid, while the fungicides penconazole and mancozeb were not. These results suggest that the insecticides may be detrimental to a biological control system using C. peregrinus while the two fungicides tested should be compatible with augmentative releases of C. peregrinus.